Longitudinal associations between response-style strategies and abnormal eating behaviors/attitudes in adolescents: a cross-lagged panel model - Yasuo Murayama; Hiroyuki Ito; Megumi Hamada; Nobuya Takayanagi; Takahiro Nakajima; Mitsunori Myogan; Masatsugu Tsujii (Journal of Eating Disorders, 2024)
Abstract Background Previous studies have suggested that response-style strategies (rumination, problem-solving, and distraction) can be risk or protective factors for the development of abnormal eating behaviors/attitudes (AEB) during adolescence. However, due to limited empirical data regarding the prospective effects of these strategies on AEB, further research is needed to clarify their role in developing AEB in adolescence. Methods This study investigated the one-year lagged effects of response-style strategies on AEB in 24,883 fourth- to eighth-grade students in Japan between 2015 and 2019 using a cross-lagged panel model. Depressive symptoms and body mass index (BMI), which are reported to relate to AEB, were also included in the analytic model. The students self-reported their levels of response-style strategies, AEB, and depressive symptoms. We also evaluated BMI based on teachers’ reports. Results We found that greater rumination significantly predicted more severe AEB in the following year among students from all grades, with small to moderate effect sizes. In addition, distraction significantly predicted more severe binge eating/purging behaviors, but with very weak small effect sizes. Problem-solving did not predict any level of AEB. Furthermore, we observed significant reciprocal relationships between response-style strategies, AEB, and depressive symptoms. Positive reciprocal associations between BMI and AEB were also found except for some intervals. Conclusions We concluded that a decrease in rumination is critical to alleviating mental health problems, such as AEB and depressive symptoms, during adolescence. This suggests that interventions to reduce the level of rumination should be conducted in the early stages of adolescence. Trial Registration Number: Not Applicable.